Fiction in "authenticity" substantiation: how the Soviet choreographers substantiated folk character of their works - I. V. Narskiy (Ukrainian Cultural Studies, 2019)
Over the decades, starting from the late 1930’s, soviet journalistic reportage about professional and mainly amateur folk dance groups from central European regions of the USSR and Siberia, Ukraine, Transcaucasia and other parts of the Soviet Union were full of reports about choreographers’ "ethnographic expeditions" down the country and their desire to "learn from the people" dance technique. Why did "field collection" of the choreographic material hold a prominent place and deserve special mention in the stories about amateur folk dance arts? Weren’t numerous stories about folk trips the invention? In the article subsequent steps are undertaken to answer these questions. Firstly, the place of amateur dance art performance in the official soviet culture and the specialists’ role of choreographic business in its development are outlined. Secondly, there is an explanation of reasons of author’s doubts in authenticity of soviet choreographers’ numerous stories about "going to the people". Thirdly, the art of dancing soviet experts’ motives, that frequently inspired them to the fictional stories about the collection of choreographic folklore are explained. Therefore, it makes an attempt to renew folk dance soviet specialists’ logic of notion about the subject of their passion, liking and professional activities. In the issue the author comes to the conclusion that ritualized stories about the analysis of folk sources by choreographer-directors were the significant argument in corroboration of "folk roots" of the soviet choreographic creative work. As the result, in the soviet discourse of folk dance the stories about choreographic "going to the people" paradoxically made instrumentalization of fiction in substantiation of "authenticity".